2018
DOI: 10.22159/ajpcr.2018.v11i10.27155
|View full text |Cite
|
Sign up to set email alerts
|

Neurorestorative Mulberries Potential of Alzheimer’s Disease in Animal Model

Abstract: Objective: Alzheimer’s disease (AD) is one of the most common neurodegenerative disorders. The present study aimed to identify the potential neurorestorative of Morus alba and Morus rubra fruits extract on aluminum chloride (AlCl3)-induced AD rats.Methods: Each Morus species extract M. alba and M. rubra at a dose 300 mg/kg body weight (b.wt.) was orally administered, daily for 6 weeks post AlCl3 induction (100 mg/kg b.wt./day/6 weeks, orally). The polyphenols content was determined according to the colorimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…According to the data manipulated in Figure 10, the behavioral test results agree with previously obtained results, which demonstrated that AlCl 3 -neurointoxicated rats took more time to catch food in a T-maze, denoting deteriorated neurocognitive function [25]. Whereas OEP extract showed a significant decrease in time taken by rats to reach food in the T-maze, in comparison to the AD-induced group, indicating improved cognitive abilities.…”
Section: Discussionsupporting
confidence: 88%
“…According to the data manipulated in Figure 10, the behavioral test results agree with previously obtained results, which demonstrated that AlCl 3 -neurointoxicated rats took more time to catch food in a T-maze, denoting deteriorated neurocognitive function [25]. Whereas OEP extract showed a significant decrease in time taken by rats to reach food in the T-maze, in comparison to the AD-induced group, indicating improved cognitive abilities.…”
Section: Discussionsupporting
confidence: 88%
“…That aside, M. alba fruit extract has significantly reversed the AlCl 3 neurotoxin-induced alteration of striatum neurotransmitters and decreased 50% of acetylcholinesterase (AChE) activity in the brain. A significant increment in norepinephrine, epinephrine, 5-hydroxytryptamine serotonin, and dopamine neurotransmitter were observed in the treated mice [ 81 ]. Based on these data, M. alba could attenuate Alzheimer’s disease via Aβ deposition alleviation, inflammatory-factor reduction, and BDNF/TrkB signaling pathway alleviation, thus proving their protective effects on memory and learning abilities.…”
Section: Nutraceutical Properties Of Morus Albamentioning
confidence: 99%
“…In previous study, the level of NA are depressed in the cortex and cerebellum of animals have administered low copper or high aluminum [38] .β-amyloid (Aβ) plaques were mostly made of aggregated Aβ proteins and neurofibrillary tangles (NFTs) formed by hyper phosphorylated tau protein. Aβ induces neurotoxicity through induction of apoptosis and inflammation, disruption of calcium homeostasis, oxidative stress, and activation of complement [39].…”
Section: Discussionmentioning
confidence: 98%